Vers une définition des constructions « tough » en anglais : les adjectifs et leur complément infinitif - Joasha Boutault (Anglophonia)
« Tough » constructions, such as this device is easy to use, have often been studied, mostly to solve the problem of the status of the syntactic subject: does it correspond to the object of the verb or is it merged into the structure in its surface position? This article focuses on the semantic and syntactic relations that the adjective entertains with its infinitival complement. Through the use of several syntactic tests and the study of genuine utterances in context, we propose a classification of « tough » constructions based on their semantico-syntactic properties. This enables us to define what we think are « true » « tough » constructions, that is to say those examples that isolate the properties of the syntactic subject in its relation to the infinitival verb.